The discovery and optimization of benzimidazoles as selective NaV1.8 blockers for the treatment of pain. Issue 1 (1st January 2019) - Brown, Alan D.; Bagal, Sharan K.; Blackwell, Paul; Blakemore, David C.; Brown, Bruce; Bungay, Peter J.; Corless, Martin; Crawforth, James; Fengas, David; Fenwick, David R.; Gray, Victoria; Kemp, Mark; et al.
Graphical abstract: Abstract: The voltage gated sodium channel NaV 1.8 has been postulated to play a key role in the transmission of pain signals. Core hopping from our previously reported phenylimidazole leads has allowed the identification of a novel series of benzimidazole NaV 1.8 blockers. Subsequent optimization allowed the identification of compound9, PF-06305591, as a potent, highly selective blocker with an excellent preclinical in vitro ADME and safety profile.